Evaluación de la sustentabilidad de fincas productoras de cacao en el cantón Babahoyo, provincia de Los Ríos - Vélez Chávez, Ayrton Donaldo (2019)
SUMMARY The present research work was carried out through a survey of 67 questions for the cacao farmers of the Las Cañitas sector, Febres Cordero parish, Babahoyo canton, in the province of Los Ríos, to raise the information and know the characteristics of the cocoa farms of producers and their problems, where unfortunately in recent years there are no study related to the sustainability. The objective of this research was the development and use of indicators and sub indicators to evaluate the sustainability in the cocoa producing farms in Babahoyo canton. The use of indicators allowed to observe clear shortcomings in the general sustainability in the ecological and sociocultural aspects. Low sustainability was observed between the different economic and ecological dimensions. From the economic point of view, food self-sufficiency was affected, in what represents A1: Diversification of production with 1.00% and the economic risk that represents, C1: Diversification of sale with 1.00%, C2: ways of trade with 0.00%, C4: area destined to cocoa cultivation with 0.00%, C5: productivity (tons) per hectare with 0.00% and C6: sources of financing with 0.00%, leaving the economic indicator with an average of 1.9, which does not reach sustainability. Among the ecology, the management of biodiversity was affected, in what A2 represents: cocoa association with 1.00%, A3: crop diversification with 1.00% and the management of the soil it represents, B1: number of applications with 1.00%, B2: row orientation with 1.00%, this leaves an average of 1.7, an ecological indicator that does not enter as sustainable either. Finally, in the sociocultural aspects, where the satisfaction of basic needs, acceptability of the production system, social integration and ecological knowledge were considered, it was sustainable with an average in the sociocultural indicator of 3.3. But nevertheless; it should be mentioned that, according to Sarandon (2009), he argues that if one of the three dimensions are not sustainable (indicators must be 2 onwards to be sustainable), the entire territory of the sector would not be sustainable. This research work concludes that the development of the indicators evaluated is adequate to detect critical points about sustainability, establish its causes and propose solutions. Keywords: Sustainability, biodiversity, diversification.